The Use of The Group Investigation Type of Cooperative Learning Model When Online Learning to Increase Students' Learning Motivation - Munggarani Kusumah Hayati; Jamaluddin Jamaluddin (Jurnal al-Thullab, 2022)
This study aims to determine the application of the Group Investigation Type cooperative learning model to the subjects of Islamic Religious Education and Character Education through online learning. This study used a quasi-experimental method. The data collection tools used were observation, interviews, tests, questionnaires, and literature studies—quantitative data analysis with a statistical approach. The results of this study are: first, the application of the group investigation type cooperative learning model with online learning is included in the particular category as indicated by the acquisition of variable X of 4.20 which is included in the interval 4.20 to 5.00. Second, the learning motivation is high if online learning using the group investigation type cooperative learning model is included in the high category as indicated by the acquisition of the Y variable of 3.92, namely at intervals. From 3.40 to 4.19. Third, the application of the Group Investigation type of cooperative learning model in online learning has a relationship with an increase in student motivation of 0.83 with a strong category including the interval 0.80-1.00. The significant influence of variable X on variable Y can influence or contribute 68.9%, while other factors influence the remaining 31.11%. Penelitian ini bertujuan untuk mengetahui penerapan model pembelajaran kooperatif tipe Group Investigation pada mata pelajaran Pendidikan Agama Islam dan Pendidikan Karakter pada siswa melalui pembelajaran daring. Penelitian ini menggunakan metode eksperimen semu. Alat pengumpulan data yang digunakan adalah observasi, wawancara, tes, angket, dan studi pustaka—analisis data kuantitatif dengan pendekatan statistik. Hasil penelitian ini adalah: pertama, penerapan model pembelajaran kooperatif tipe group investigation dengan pembelajaran online termasuk dalam kategori khusus yang ditunjukkan dengan perolehan variabel X sebesar 4,20. yang termasuk dalam interval 4.20 sampai 5.00. Kedua, motivasi belajar siswa terkategori tinggi jika pembelajaran daring dengan model pembelajaran kooperatif tipe group investigation termasuk dalam kategori tinggi yang ditunjukkan dengan perolehan variabel Y sebesar 3,92 yaitu pada interval. Dari 3,40 hingga 4,19. Ketiga, penerapan model pembelajaran kooperatif tipe Group Investigation dalam pembelajaran online memiliki hubungan dengan peningkatan motivasi belajar siswa sebesar 0,83 dengan kategori kuat termasuk interval 0,80-1,00. Pengaruh signifikan variabel X terhadap variabel Y dapat mempengaruhi atau memberikan kontribusi sebesar 68,9%, sedangkan faktor lain mempengaruhi sisanya sebesar 31,11%.